Environment-friendly direct-modification recycling agent for asphalt pavement recycling material and preparation method thereof
Patent Information
- Application Number
- CN202610801652.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-23
AI Technical Summary
然而,沥青路面回收料普遍存在轻质组分流失、沥青质含量升高、分子链团聚严重、粘结性能大幅衰减等问题,导致再生沥青混合料存在低温抗裂性差、高温稳定性不足、水稳定性弱、新旧沥青界面融合性差等缺陷,严重制约废旧沥青回收料的高比例、高质量再生利用
本申请中公开了一种适用于沥青路面回收料的环保型直投改性再生剂及其制备方法,通过将废旧轮胎胶粉与废旧尼龙纤维熔融共混并经马来酸酐接枝,实现了高分子废弃物的资源化利用,赋予再生剂高活性的界面反应位点;随后引入环氧大豆油与双氧水进行原位环氧化与氧化改性,显著提升了再生剂与沥青路面回收料的相容性及化学键合能力;最终复配超支化聚酯与复合填料,利用多维增强与增塑协同作用,制得的改性再生剂不仅能高效激活沥青路面回收料中的惰性组分以恢复其流变性能,还能在沥青路面回收料中构建橡胶、纤维和填料的三维增强网络,同步实现废旧料循环利用、沥青高附加值再生,实现对沥青路面回收料的稳定性、抗开裂性能和抗水损害性能的综合提升;
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the technical field of asphalt pavement materials, and in particular to an environmentally friendly direct-injection modified regenerator suitable for asphalt pavement recycled materials and its preparation method. Background Technology
[0002] During long-term service, asphalt pavements are susceptible to various damages such as asphalt aging, aggregate loosening, pavement cracking, and potholes due to the combined effects of sunlight, rainwater erosion, temperature cycles, and vehicle loads, resulting in a large amount of waste asphalt pavement recycled material. The recycling of waste asphalt pavement material is an important direction for the green and resource-based development of road engineering. However, recycled asphalt pavement materials generally suffer from problems such as loss of lightweight components, increased asphalt content, severe molecular chain aggregation, and significant reduction in bonding performance. This leads to defects in recycled asphalt mixtures, including poor low-temperature crack resistance, insufficient high-temperature stability, weak water stability, and poor interface integration between new and old asphalt, severely restricting the high-proportion, high-quality recycling of waste asphalt pavement material.
[0003] Currently, the industry typically uses recycling agents to reconstitute and repair the properties of recycled asphalt pavement. Conventional recycling agents are mostly composed of single oil components and small-molecule plasticizers, which can only simply supplement the missing lightweight components in recycled asphalt pavement. Their function is limited, and their modification dimensions are limited. They cannot repair the cross-linking defects of recycled asphalt pavement at the molecular structure level, making it difficult to improve the toughness and structural stability of the asphalt matrix. Furthermore, existing recycling agents generally suffer from poor compatibility with waste asphalt mixtures, weak penetration and wetting ability, and low interfacial bond strength. After long-term service, recycled asphalt pavement is prone to cracking, loosening, and peeling, resulting in a short service life.
[0004] Existing technologies have included some solutions that use rubber powder, fiber, and other auxiliary materials to modify recycling agents. However, most of these solutions suffer from problems such as limited auxiliary material compatibility, weak interfacial bonding, and crude blending modification processes. Conventional simple blending methods cannot achieve effective interfacial fusion between rubber powder, fiber, and asphalt matrix. The two-phase interface is prone to delamination and debonding, making it difficult to simultaneously improve the high-temperature rutting resistance and low-temperature crack resistance of recycled asphalt. Furthermore, existing technologies do not design grafting modification, swelling activation, oxidative degradation, and hyperbranching crosslinking synergistic modification processes for waste rubber powder and waste nylon fiber systems. The auxiliary materials have insufficient activity and poor dispersion uniformity, failing to fully leverage the toughening, reinforcing, and anti-aging advantages of waste polymer materials, resulting in limited overall modification effects of recycling agents.
[0005] In addition, existing recycling agent formulation systems lack targeted synergistic design for esterification crosslinking, plasticizing compatibility, and interface activation. The internal structural stability of the recycling system is poor, the toughening and reinforcing effect is weak, and it is difficult to take into account the mechanical strength, temperature stability and durability of recycled asphalt. Therefore, it cannot meet the high-quality recycling construction requirements of high-volume waste asphalt recycled materials.
[0006] Therefore, how to utilize waste tire rubber powder and waste nylon fiber to achieve synergistic modification, and solve the technical problems of the single modification effect of existing recycling agents, poor stability, crack resistance and water damage resistance of recycled asphalt, and low resource utilization rate, has become an urgent technical problem to be solved in the field of asphalt pavement recycling technology. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this application provides an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recyclables and its preparation method.
[0008] In a first aspect, this application provides a method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recycled materials, employing the following technical solution: A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recyclables, the specific steps of which are as follows: (1) Waste tire rubber powder and waste nylon fiber are melt-blended and maleic anhydride is added to carry out a grafting reaction to obtain the first mixture; (2) Add epoxidized soybean oil to the first mixture and knead it in an intensive kneading process, then add hydrogen peroxide and knead it in an intensive kneading process to obtain the second mixture; (3) Add hyperbranched polyester, plasticizer, esterification catalyst and composite filler to the second mixture and then mix them to obtain the third mixture; (4) The third mixture is melt-extruded and granulated by a twin-screw extruder and dried to obtain the modified regenerator.
[0009] By adopting the above technical solution, this preparation method realizes the resource utilization of polymeric waste by melt-blending waste tire rubber powder with waste nylon fiber and grafting with maleic anhydride, giving the regenerator highly active interfacial reaction sites. Subsequently, epoxidized soybean oil and hydrogen peroxide are introduced for in-situ epoxidation and oxidative modification, which significantly improves the compatibility and chemical bonding ability between the regenerator and asphalt pavement recycled material. Finally, hyperbranched polyester and composite filler are compounded, and the modified regenerator prepared by utilizing the synergistic effect of multidimensional reinforcement and plasticization can not only efficiently activate the inert components in asphalt pavement recycled material to restore its rheological properties, but also construct a three-dimensional reinforcement network of rubber, fiber and filler in the asphalt matrix, simultaneously realizing the recycling of waste materials and high-value-added regeneration of asphalt, and achieving a comprehensive improvement in the stability, crack resistance and water damage resistance of asphalt pavement recycled material.
[0010] Preferably, the melt blending temperature in step (1) is 320-380℃, and the melt blending time is 10-20 minutes; Preferably, the grafting reaction time of maleic anhydride in step (1) is 5-10 minutes.
[0011] Preferably, in step (2), the temperature for adding epoxidized soybean oil and mixing is 80-100℃, and the mixing time is 30-60min.
[0012] Preferably, the time for adding hydrogen peroxide and mixing in step (2) is 5-10 minutes.
[0013] Preferably, the temperature for intensive mixing in step (3) is 140-160°C and the mixing time is 5-15 minutes.
[0014] Preferably, in step (1), the mass ratio of waste tire rubber powder to waste nylon fiber is 1:(0.2-0.4).
[0015] Preferably, the amount of maleic anhydride added in step (1) is 2-4% of the total amount of waste tire rubber powder and waste nylon fiber.
[0016] Preferably, the amount of epoxidized soybean oil added in step (2) is 7.8-18.5% of the total amount of waste tire rubber powder and waste nylon fiber added.
[0017] Preferably, the amount of hydrogen peroxide added in step (2) is 2.6-9.3% of the total amount of waste tire rubber powder and waste nylon fiber.
[0018] Preferably, the amount of the second mixture added in step (3) is 120-205 parts by mass.
[0019] Preferably, the amount of hyperbranched polyester added in step (3) is 5-10% of the amount of the second mixture added.
[0020] Preferably, the amount of plasticizer added in step (3) is 3-6% of the amount of the second mixture added.
[0021] Preferably, the amount of esterification catalyst added in step (3) is 0.14-2.31% of the amount of the second mixture added.
[0022] Preferably, the amount of composite filler added in step (3) is 2-5% of the amount of the second mixture added.
[0023] Preferably, the composite filler in step (3) comprises the following raw material components in parts by mass: 200-300 parts of silica nanocomposite material, 90-110 parts of sodium montmorillonite, 0.5-1.5 parts of hexadecyltrimethylammonium bromide (first part), 15-25 parts of silane coupling agent (first part), 180-220 parts of ethanol, 100-200 parts of sodium silicate (first part), 60-80 parts of hydrochloric acid, 2-5 parts of hexadecyltrimethylammonium bromide (second part), 10-30 parts of carbon black, 8-10 parts of sodium hydroxide, 80-120 parts of lignocellulose, 350-450 parts of montmorillonite, and 10-15 parts of silane coupling agent (second part).
[0024] Preferably, the silica nanocomposite material comprises the following raw material components in parts by weight: 300-400 parts sodium disilicate, 10-20 parts sodium sulfate, 5-10 parts polyethylene glycol, 100-150 parts n-heptane, 20-40 parts sulfuric acid, 50-100 parts 11-aminoundecanoic acid, and 0.5-1 parts antioxidant 1010.
[0025] Preferably, the preparation method of the silica nanocomposite material includes the following steps: mixing sodium disilicate and sodium sulfate, adding polyethylene glycol and n-heptane and mixing, and then adding sulfuric acid and mixing to obtain a mixed solution; After mixing 11-aminoundecanoic acid, antioxidant 1010, and the mixed solution, the mixture was dried to obtain a mixed powder. The mixed powders were polymerized under vacuum to obtain a silica nanocomposite material.
[0026] By adopting the above technical solution, this application improves the raw materials of the composite filler by adding silica nanocomposite materials. The added silica nanocomposite materials are polymerized in situ on the silica surface to construct an organic hybrid shell composed of 11-aminoundecanoic acid and antioxidant 1010. This structure not only improves the interfacial compatibility between nano-silica and asphalt by utilizing long carbon chains and inhibits the agglomeration of inorganic particles, but also achieves nanoscale uniform distribution of antioxidant components in the asphalt matrix through the chemical anchoring of antioxidant 1010. Thus, while restoring the flexibility of recycled asphalt pavement, it also provides a long-lasting thermo-oxidative stabilization barrier.
[0027] Preferably, the preparation method of the composite filler includes the following steps: mixing sodium montmorillonite and a first portion of hexadecyltrimethylammonium bromide, adding a first silane coupling agent and ethanol, and mixing to obtain mixture 1; Sodium silicate and hydrochloric acid were mixed, and then hexadecyltrimethylammonium bromide and carbon black were added and mixed to obtain mixture 2. Sodium hydroxide and lignocellulose were mixed, and then montmorillonite was added and mixed to obtain mixture 3; Mixture 1, mixture 2, and mixture 3 are mixed together, and then a second silane coupling agent and a silica nanocomposite material are added and mixed to obtain a composite filler.
[0028] By employing the above technical solution, during the preparation of mixture 1, sodium-based montmorillonite is organically intercalated using hexadecyltrimethylammonium bromide, and its surface is functionalized using a first silane coupling agent. This dual modification significantly expands the interlayer spacing of montmorillonite, reduces its surface polarity, allowing it to fully swell and disperse in the asphalt system. The physical barrier effect of the layered structure blocks the penetration paths of oxygen and moisture, enhancing the stability and anti-aging ability of the recycled asphalt.
[0029] In the preparation of mixture 2, nano-silica is precipitated in the liquid phase by the in-situ reaction of sodium silicate and hydrochloric acid, and forms a zero-dimensional hybrid reinforcing phase with carbon black. This mixture, with its extremely high specific surface area, generates adsorption and slow-release effects, which can lock in the light components lost from the recycled asphalt pavement material or the externally added recycled oil, preventing their volatilization and migration in the short term; at the same time, the introduction of carbon black provides excellent ultraviolet shielding function and rigid support, compensating for the decrease in high-temperature strength of asphalt caused by simple recycling.
[0030] In the preparation of mixture 3, lignocellulose was activated with sodium hydroxide and then combined with montmorillonite to form micron-scale reinforcing units. The activated lignocellulose surface is rich in hydroxyl groups, forming a microfiber entanglement network in the asphalt. Through crack bridging and energy dissipation mechanisms, it significantly improves the low-temperature crack resistance and fatigue durability of recycled asphalt, solving the problem that traditional recycling agents tend to make asphalt brittle.
[0031] The components of mixture 1, mixture 2, mixture 3, and silica nanocomposite are integrated into an organic whole via a second silane coupling agent. This filler achieves a synergistic effect of physical regeneration and chemical modification: the porous montmorillonite and silica are responsible for regulating the balance between asphaltene and resin to restore rheological properties, while the nano-reinforcing phase and fiber toughening phase together construct a three-dimensional network skeleton to support mechanical strength. This allows the recycled asphalt pavement material to restore its working performance while comprehensively improving its stability, crack resistance, and water damage resistance.
[0032] Secondly, this application provides an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recycled materials, employing the following technical solution: An environmentally friendly direct-injection modified recycler suitable for asphalt pavement recycled materials is prepared using the above method.
[0033] In summary, this application includes at least one of the following beneficial technical effects: This application discloses an environmentally friendly direct-injection modified regenerator suitable for asphalt pavement recycled materials and its preparation method. By melt-blending waste tire rubber powder with waste nylon fiber and grafting with maleic anhydride, the resource utilization of polymeric waste is realized, giving the regenerator highly active interfacial reaction sites. Subsequently, epoxidized soybean oil and hydrogen peroxide are introduced for in-situ epoxidation and oxidative modification, which significantly improves the compatibility and chemical bonding ability between the regenerator and asphalt pavement recycled materials. Finally, hyperbranched polyester and composite fillers are compounded, and the modified regenerator prepared by utilizing the synergistic effect of multidimensional reinforcement and plasticization can not only efficiently activate the inert components in asphalt pavement recycled materials to restore their rheological properties, but also construct a three-dimensional reinforcing network of rubber, fiber and filler in asphalt pavement recycled materials, simultaneously realizing the recycling of waste materials and high-value-added regeneration of asphalt, and achieving a comprehensive improvement in the stability, crack resistance and water damage resistance of asphalt pavement recycled materials. This application makes full use of waste tire rubber powder and waste nylon fiber. The raw materials are simple and readily available, which can save costs, eliminate environmental pollution, and improve the performance of asphalt. Detailed Implementation
[0034] The technical solutions of this application are further illustrated by specific embodiments below. These specific embodiments do not represent a limitation on the scope of protection of this application. Any non-essential modifications and adjustments made by others based on the concept of this application still fall within the scope of protection of this application.
[0035] All raw materials involved in this application are commercially available products, among which, 11-Aminoundecanoic acid, purchased from the Institute of Polymer and Bioengineering, North University of China, with a purity greater than 96%; Sodium silicate was purchased from Shanxi Tongde Chemical Co., Ltd. Polyethylene glycol, polyethylene glycol 6000 (PEG): Tianjin Huadong Reagent Factory; Sodium-based montmorillonite, Shijiazhuang Tengrui Mineral Products Trading Co., Ltd.; Carbon black, grade N330, Wuhai Black Cat Carbon Black Co., Ltd.; Lignocellulose, Wuhan Huadong Chemical Co., Ltd.; Montmorillonite, grade DK-3, Zhejiang Fenghong Clay Co., Ltd.; The hyperbranched polyester was purchased from Angxing New Carbon Materials Changzhou Co., Ltd., with an average hydroxyl number of 6-24 and a hydroxyl value of 400-700 mg KOH / g; Epoxidized soybean oil, CAS No.: 8013-07-8; The present application will be further described in detail below with reference to embodiments and comparative examples.
[0036] A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recycled materials, comprising the following steps: (1) Mix waste tire rubber powder with waste nylon fiber, add it to a mixer, melt and blend at 320-380℃ for 10-20 minutes, then add maleic anhydride, continue to mix for 5-10 minutes to carry out grafting reaction, and obtain the first mixture; (2) Add epoxidized soybean oil to the first mixture and knead it at 80℃-100℃ for 30-60 minutes to induce swelling. Then add hydrogen peroxide and continue kneading at the same temperature for 5-10 minutes to promote the oxidative degradation of waste tire rubber powder and waste nylon fiber, and obtain the second mixture. (3) Add hyperbranched polyester, plasticizer, esterification catalyst and composite filler to the second mixture, and knead at 140-160℃ for 5-15 minutes to obtain the third mixture; (4) The third mixture is melt-extruded and granulated by a twin-screw extruder and then dried by hot air to obtain the modified regenerator.
[0037] In one specific implementation scheme, the mass ratio of waste tire rubber powder to waste nylon fiber in step (1) is 1:(0.2-0.4).
[0038] In one specific implementation scheme, the amount of maleic anhydride added in step (1) is 2-4% of the total amount of waste tire rubber powder and waste nylon fiber.
[0039] In one specific implementation scheme, the amount of epoxidized soybean oil added in step (2) is 7.8-18.5% of the total amount of waste tire rubber powder and waste nylon fiber added.
[0040] In one specific implementation scheme, the amount of hydrogen peroxide added in step (2) is 2.6-9.3% of the total amount of waste tire rubber powder and waste nylon fiber added.
[0041] In one specific implementation, the amount of the second mixture added in step (3) is 120-205 parts by mass.
[0042] In one specific implementation, the amount of hyperbranched polyester added in step (3) is 5-10% of the amount of the second mixture added.
[0043] In one specific implementation, the amount of plasticizer added in step (3) is 3-6% of the amount of the second mixture added.
[0044] In one specific implementation, the amount of esterification catalyst added in step (3) is 0.14-2.31% of the amount of the second mixture added.
[0045] In one specific implementation, the amount of composite filler added in step (3) is 2-5% of the amount of the second mixture added.
[0046] In one specific implementation scheme, the composite filler in step (3) comprises the following raw material components in parts by mass: 200-300 parts of silica nanocomposite material, 90-110 parts of sodium montmorillonite, 0.5-1.5 parts of hexadecyltrimethylammonium bromide (first part), 15-25 parts of silane coupling agent (first part), 180-220 parts of ethanol, 100-200 parts of sodium silicate (first part), 60-80 parts of hydrochloric acid, 2-5 parts of hexadecyltrimethylammonium bromide (second part), 10-30 parts of carbon black, 8-10 parts of sodium hydroxide, 80-120 parts of lignocellulose, 350-450 parts of montmorillonite, and 10-15 parts of silane coupling agent (second part).
[0047] In one specific implementation, the silica nanocomposite material comprises the following raw material components in parts by weight: 300-400 parts sodium disilicate, 10-20 parts sodium sulfate, 5-10 parts polyethylene glycol, 100-150 parts n-heptane, 20-40 parts sulfuric acid, 50-100 parts 11-aminoundecanoic acid, and 0.5-1 parts antioxidant 1010.
[0048] In one specific implementation, the preparation method of the silica nanocomposite material includes the following steps: mixing sodium disilicate and sodium sulfate, adding polyethylene glycol and n-heptane and mixing, and then adding sulfuric acid and mixing to obtain a mixed solution; After mixing 11-aminoundecanoic acid, antioxidant 1010, and the mixed solution, the mixture was dried to obtain a mixed powder. The mixed powders were polymerized under vacuum to obtain a silica nanocomposite material.
[0049] In one specific implementation scheme, the preparation method of the composite filler includes the following steps: mixing sodium montmorillonite and a first portion of hexadecyltrimethylammonium bromide, adding a first silane coupling agent and ethanol, and mixing to obtain mixture 1; Sodium silicate and hydrochloric acid were mixed, and then hexadecyltrimethylammonium bromide and carbon black were added and mixed to obtain mixture 2. Sodium hydroxide and lignocellulose were mixed, and then montmorillonite was added and mixed to obtain mixture 3; Mixture 1, mixture 2, and mixture 3 are mixed together, and then a second silane coupling agent and a silica nanocomposite material are added and mixed to obtain a composite filler.
[0050] Preparation Example 1:
[0051] A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recycled materials, comprising the following steps: (1) Preparation of silica nanocomposites Mix 350g of sodium disilicate and 650g of water, add 15g of sodium sulfate, stir at 50°C for 20 minutes, raise the temperature to 70°C, add 8g of polyethylene glycol and 130g of n-heptane and mix for 30 minutes, raise the temperature to 80°C, add 30g of sulfuric acid dropwise, and react for 60 minutes after the addition is complete to obtain a mixed solution. Mix 80g of 11-aminoundecanoic acid, 0.8g of antioxidant 1010, and the mixed solution, and dry to obtain a mixed powder; The mixed powder was placed in the device, evacuated and then filled with nitrogen, and repeated 6 times until the vacuum degree reached above 0.09. The mixed powder was heated to 90°C and held at that temperature for 10 minutes. Then the temperature was increased to 230°C at a rate of 10°C every 0.5 hours and held at that temperature for 4 hours to allow the polymerization reaction to be complete. The mixture was then cooled to room temperature to obtain the silica nanocomposite material.
[0052] (2) Preparation of composite fillers 100g of sodium montmorillonite and 500g of water were mixed for 5 hours to obtain a sodium montmorillonite mixed solution. Mix 1 g of hexadecyltrimethylammonium bromide and 1 mL of hydrochloric acid for 20 minutes, add sodium montmorillonite mixed solution and mix for 10 minutes, filter, add 20 g of first silane coupling agent KH550 and 200 g of ethanol to the filter and mix for 20 minutes to obtain mixture 1; 150g of sodium monosilicate and 70g of hydrochloric acid were mixed evenly, and 3g of hexadecyltrimethylammonium bromide and 20g of carbon black were added and mixed for 3 hours. After the reaction was completed, the mixture was aged at room temperature for 10 hours, and the solid was collected by centrifugation to obtain mixture 2. 9g of sodium hydroxide and 100g of lignocellulose were mixed for 20 minutes, then 400g of montmorillonite and 1500g of water were added. The mixture was then mixed at 80℃ for 3 hours and dried to obtain mixture 3. Mixtures 1, 2, and 3 are mixed together, and then 13g of the second silane coupling agent KH570, 30g of ethanol, and 250g of silica nanocomposite material are added and mixed. The mixture is then dried to obtain the composite filler.
[0053] Preparation Example 2:
[0054] A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recycled materials, comprising the following steps: (1) Preparation of silica nanocomposites Mix 300g of sodium disilicate and 650g of water, add 10g of sodium sulfate, stir at 50°C for 20 minutes, raise the temperature to 70°C, add 5g of polyethylene glycol and 100g of n-heptane and mix for 30 minutes, raise the temperature to 80°C, add 20g of sulfuric acid dropwise, and react for 60 minutes after the addition is complete to obtain a mixed solution. Mix 50g of 11-aminoundecanoic acid, 0.5g of antioxidant 1010, and the mixed solution, and dry to obtain a mixed powder; The mixed powder was placed in the device, evacuated and then filled with nitrogen, and repeated 6 times until the vacuum degree reached above 0.09. The mixed powder was heated to 90°C and held at that temperature for 10 minutes. Then the temperature was increased to 230°C at a rate of 10°C every 0.5 hours and held at that temperature for 4 hours to allow the polymerization reaction to be complete. The mixture was then cooled to room temperature to obtain the silica nanocomposite material.
[0055] (2) Preparation of composite fillers 90g of sodium montmorillonite and 500g of water were mixed for 5 hours to obtain a sodium montmorillonite mixed solution. Mix 0.5 g of hexadecyltrimethylammonium bromide and 1 mL of hydrochloric acid for 20 minutes, add sodium montmorillonite mixed solution and mix for 10 minutes, filter, add 15 g of first silane coupling agent KH550 and 180 g of ethanol to the filter and mix for 20 minutes to obtain mixture 1; 100g of sodium monosilicate and 60g of hydrochloric acid were mixed evenly, and 2g of hexadecyltrimethylammonium bromide and 10g of carbon black were added and mixed for 3 hours. After the reaction was completed, the mixture was aged at room temperature for 10 hours, and the solid was collected by centrifugation to obtain mixture 2. Mix 8g of sodium hydroxide and 80g of lignocellulose for 20 minutes, add 350g of montmorillonite and 1500g of water, mix at 80℃ for 3 hours, and dry to obtain mixture 3; Mixtures 1, 2, and 3 are mixed together, and then 10g of the second silane coupling agent KH570, 20g of ethanol, and 200g of silica nanocomposite material are added and mixed. The mixture is then dried to obtain the composite filler.
[0056] Preparation Example 3:
[0057] A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recycled materials, comprising the following steps: (1) Preparation of silica nanocomposites Mix 400g of sodium disilicate and 650g of water, add 20g of sodium sulfate, stir at 50°C for 20 minutes, raise the temperature to 70°C, add 10g of polyethylene glycol and 150g of n-heptane, mix for 30 minutes, raise the temperature to 80°C, add 40g of sulfuric acid dropwise, and react for 60 minutes after the addition is complete to obtain a mixed solution. 100g of 11-aminoundecanoic acid, 1g of antioxidant 1010, and the mixed solution were mixed and dried to obtain a mixed powder. The mixed powder was placed in the device, evacuated and then filled with nitrogen, and repeated 6 times until the vacuum degree reached above 0.09. The mixed powder was heated to 90°C and held at that temperature for 10 minutes. Then the temperature was increased to 230°C at a rate of 10°C every 0.5 hours and held at that temperature for 4 hours to allow the polymerization reaction to be complete. The mixture was then cooled to room temperature to obtain the silica nanocomposite material.
[0058] (2) Preparation of composite fillers 110g of sodium montmorillonite and 500g of water were mixed for 5 hours to obtain a sodium montmorillonite mixed solution. Mix 1.5 g of hexadecyltrimethylammonium bromide and 1 mL of hydrochloric acid for 20 minutes, add sodium montmorillonite mixed solution and mix for 10 minutes, filter, add 25 g of first silane coupling agent KH550 and 220 g of ethanol to the filter and mix for 20 minutes to obtain mixture 1; 200g of sodium monosilicate and 80g of hydrochloric acid were mixed evenly, and 5g of hexadecyltrimethylammonium bromide and 30g of carbon black were added and mixed for 3 hours. After the reaction was completed, the mixture was aged at room temperature for 10 hours, and the solid was collected by centrifugation to obtain mixture 2. Mix 10g of sodium hydroxide and 120g of lignocellulose for 20 minutes, add 450g of montmorillonite and 1500g of water, mix at 80℃ for 3 hours, and dry to obtain mixture 3; Mixtures 1, 2, and 3 are mixed together, and then 15g of the second silane coupling agent KH570, 40g of ethanol, and 300g of silica nanocomposite material are added and mixed. The mixture is then dried to obtain the composite filler.
[0059] Example 1:
[0060] An environmentally friendly direct-injection modified regenerator suitable for asphalt pavement recycled materials comprises the following raw material components in parts by weight: 100g waste tire rubber powder, 30g waste nylon fiber, 3.9g maleic anhydride, 17.1g epoxidized soybean oil, 7.7g hydrogen peroxide, 15g hyperbranched polyester, 9g plasticizer, 1.23g esterification catalyst, and 5.55g composite filler.
[0061] The plasticizer is dibutyl sebacate; The esterification catalyst is p-toluenesulfonic acid; The composite filler was prepared in Preparation Example 1.
[0062] A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recyclables, the specific steps of which are as follows: (1) Waste tire rubber powder and waste nylon fiber were melt-blended at 350°C for 15 minutes, and maleic anhydride was added for grafting reaction for 8 minutes to obtain the first mixture; (2) Add epoxidized soybean oil to the first mixture, knead at 90°C for 45 minutes, add hydrogen peroxide and knead for 8 minutes to obtain the second mixture; (3) Add hyperbranched polyester, plasticizer, esterification catalyst and composite filler to 158.7g of the second mixture and mix at 150°C for 10 minutes to obtain the third mixture; (4) The third mixture is melt-extruded and granulated by a twin-screw extruder and dried to obtain the modified regenerator.
[0063] The four extrusion temperatures of the twin-screw extruder are 150℃, 155℃, 160℃, and 170℃, with a cycle extrusion time of 5 minutes and a screw speed of 40-60 r / min.
[0064] Example 2:
[0065] An environmentally friendly direct-injection modified recycler suitable for asphalt pavement recycled materials comprises the following raw material components in parts by weight: 90g waste tire rubber powder, 18g waste nylon fiber, 2.16g maleic anhydride, 8.42g epoxidized soybean oil, 2.81g hydrogen peroxide, 6.07g hyperbranched polyester, 3.64g plasticizer, 0.17g esterification catalyst, and 2.43g composite filler.
[0066] The plasticizer is dibutyl sebacate; The esterification catalyst is p-toluenesulfonic acid; The composite filler was prepared in Preparation Example 2.
[0067] A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recyclables, the specific steps of which are as follows: (1) Waste tire rubber powder and waste nylon fiber were melt-blended at 320°C for 10 minutes, and maleic anhydride was added for grafting reaction for 5 minutes to obtain the first mixture; (2) Add epoxidized soybean oil to the first mixture, knead at 80°C for 30 minutes, add hydrogen peroxide and knead for 5 minutes to obtain the second mixture; (3) Add hyperbranched polyester, plasticizer, esterification catalyst and composite filler to 121.39g of the second mixture and mix at 140°C for 5 minutes to obtain the third mixture; (4) The third mixture is melt-extruded and granulated by a twin-screw extruder and dried to obtain the modified regenerator.
[0068] The four extrusion temperatures of the twin-screw extruder are 150℃, 155℃, 160℃, and 170℃, with a cycle extrusion time of 5 minutes and a screw speed of 40-60 r / min.
[0069] Example 3:
[0070] An environmentally friendly direct-injection modified recycler suitable for asphalt pavement recycled materials comprises the following raw material components in parts by weight: 110g waste tire rubber powder, 44g waste nylon fiber, 6.2g maleic anhydride, 28.5g epoxidized soybean, 14.3g hydrogen peroxide, 20.3g hyperbranched polyester, 12.2g plasticizer, 4.7g esterification catalyst, and 10.15g composite filler.
[0071] The plasticizer is dibutyl sebacate; The esterification catalyst is p-toluenesulfonic acid; The composite filler was prepared in Preparation Example 3.
[0072] A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement recyclables, the specific steps of which are as follows: (1) Waste tire rubber powder and waste nylon fiber were melt-blended at 380°C for 20 minutes, and maleic anhydride was added for grafting reaction for 10 minutes to obtain the first mixture; (2) Add epoxidized soybean oil to the first mixture, knead at 100°C for 60 minutes, add hydrogen peroxide and knead for 10 minutes to obtain the second mixture; (3) Add hyperbranched polyester, plasticizer, esterification catalyst and composite filler to 203g of the second mixture and mix at 160°C for 15 minutes to obtain the third mixture; (4) The third mixture is melt-extruded and granulated by a twin-screw extruder and dried to obtain the modified regenerator.
[0073] The four extrusion temperatures of the twin-screw extruder are 150℃, 155℃, 160℃, and 170℃, with a cycle extrusion time of 5 minutes and a screw speed of 40-60 r / min.
[0074] Example 4:
[0075] The difference from Example 1 is that the composite filler was prepared by Preparation Example 2.
[0076] Example 5:
[0077] The difference from Example 1 is that the composite filler was prepared by Preparation Example 3.
[0078] Example 6:
[0079] The difference from Example 1 is that the amount of composite filler added is 3.174g, that is, the amount of composite filler added is 2% of the amount of the second mixture added.
[0080] Example 7:
[0081] The difference from Example 1 is that the amount of composite filler added is 7.935g, that is, the amount of composite filler added is 5% of the amount of the second mixture added.
[0082] Comparative Example 1:
[0083] The difference from Example 1 is that no composite filler is added.
[0084] Comparative Example 2:
[0085] The difference from Example 1 is that the amount of composite filler added is 3.0153g, that is, the amount of composite filler added is 1.9% of the amount of the second mixture added.
[0086] Comparative Example 3:
[0087] The difference from Example 1 is that the amount of composite filler added is 8.0937g, that is, the amount of composite filler added is 5.1% of the amount of the second mixture added.
[0088] Application example:
[0089] The modified recycling agents prepared in the above embodiments and comparative examples are applied to the preparation of asphalt pavement materials, and the specific methods are as follows: A construction method for an asphalt pavement material includes the following steps: (1) Place 60 kg of waste asphalt mixture (i.e. asphalt pavement recycling material) that has been milled, crushed and screened in an oven at 100℃ and dry it. (2) The waste asphalt mixture and 5 kg of modified recycling agent are subjected to high-speed shearing at 8000 rpm for 50 minutes at 160℃, and the mixture is stirred evenly to obtain asphalt pavement material.
[0090] The modified regenerator was prepared in the above examples or comparative examples.
[0091] Performance testing:
[0092] 1. Performance restoration of waste asphalt The asphalt pavement material prepared in the application example was used to construct a renovated asphalt pavement, and the penetration and ductility of the renovated asphalt pavement were used as evaluations of the restoration.
[0093] The penetration test, conducted according to the current domestic testing standard (JTJ 052T 0604-93), uses the following test conditions: P 25℃, 100g, 5s. Penetration reflects the consistency of asphalt pavement materials.
[0094] Ductility was measured using a ductility tester. Asphalt samples were prepared into figure-eight shaped standard specimens (minimum cross-section 1 cm). 2 Ductility is defined as the length (in cm) at which the asphalt pavement breaks under specified tensile speed and temperature. The asphalt pavement material prepared in the application example was laid on an asphalt pavement, and its ductility at 15°C was tested.
[0095] Table 1 Performance Restoration of Waste Asphalt
[0096] As shown in Table 1, when the modified recycling agent prepared in this application is mixed with waste asphalt mixture (i.e. asphalt pavement recycled material), the asphalt pavement material prepared has a high degree of recovery after construction, and the penetration and ductility are significantly improved.
[0097] 2. Stability and dynamic stability testing The asphalt pavement material prepared in the application example was used to construct a renovated asphalt pavement, and the stability and dynamic stability of the renovated asphalt pavement were used as evaluations of the restoration.
[0098] Table 2. Results of stability and dynamic stability tests
[0099] As shown in Table 2, the modified recycling agent prepared in this application is mixed with waste asphalt mixture (i.e. asphalt pavement recycled material). The refurbished asphalt prepared by the asphalt pavement material meets the requirements of the industry standard "Technical Specification for Construction of Highway Asphalt Pavement" (JTGF40-2004) and can be directly used for pavement material service.
[0100] 3. Testing of crack resistance and water damage resistance According to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011), asphalt pavement materials prepared in the application example were used to prepare test specimens. The workability of the asphalt pavement materials was evaluated by the mixing time, the crack resistance of the mixture was evaluated by the splitting strength index, and the water loss resistance of the mixture was evaluated by the freeze-thaw splitting strength ratio (TSR). The test results are shown in Table 3.
[0101] Table 3. Test results of crack resistance and water damage resistance
[0102] As shown in Table 3, mixing the modified recycling agent prepared in this application with waste asphalt mixture (i.e., recycled asphalt pavement material) to prepare asphalt pavement material can significantly improve the crack resistance and water damage resistance of asphalt pavement material, which is beneficial to improving the road performance of asphalt pavement material. The asphalt pavement material prepared by mixing the modified recycling agent prepared in this application with waste asphalt mixture (i.e., recycled asphalt pavement material) has a mixing time greater than 120 seconds, meeting the relevant specifications.
[0103] Based on the test results of Example 1 and Comparative Example 1 of this application, it can be seen that the performance test results of Example 1 are better than those of Comparative Example 1. This indicates that by improving the raw materials of the modified recycling agent and adding composite fillers, the synergistic effect between the composite fillers and other raw materials can effectively improve the crack resistance and water damage resistance of asphalt pavement materials.
[0104] Based on the test results of Examples 1, 6, 7, Comparative Examples 2 and 3, it can be seen that the amount of composite filler added affects the performance of the modified regenerator, and the modified regenerator prepared has the best overall performance when the amount of composite filler added is 2-5% of the amount of the second mixture added.
Claims
1. A method for preparing an environmentally friendly direct-injection modified recycling agent suitable for asphalt pavement reclaimed materials, characterized in that, The specific steps are as follows: (1) Waste tire rubber powder and waste nylon fiber are melt-blended and maleic anhydride is added to carry out a grafting reaction to obtain the first mixture; (2) Add epoxidized soybean oil to the first mixture and knead it in an intensive kneading process, then add hydrogen peroxide and knead it in an intensive kneading process to obtain the second mixture; (3) Add hyperbranched polyester, plasticizer, esterification catalyst and composite filler to the second mixture and then mix them to obtain the third mixture; (4) The third mixture is melt-extruded and granulated by a twin-screw extruder and dried to obtain the modified regenerator.
2. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recyclable materials according to claim 1, characterized in that: The melting and blending temperature in step (1) is 320-380℃, and the melting and blending time is 10-20 minutes; In step (1), the grafting reaction time with maleic anhydride is 5-10 minutes.
3. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recyclable materials according to claim 1, characterized in that: In step (2), the temperature for adding epoxidized soybean oil and mixing is 80-100℃, and the mixing time is 30-60 minutes. The time for adding hydrogen peroxide and mixing in step (2) is 5-10 minutes.
4. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recyclable materials according to claim 1, characterized in that: The temperature for intensive mixing in step (3) is 140-160℃, and the mixing time is 5-15 minutes.
5. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recyclable materials according to claim 1, characterized in that: In step (1), the mass ratio of waste tire rubber powder to waste nylon fiber is 1:(0.2-0.4); the amount of maleic anhydride added is 2-4% of the total amount of waste tire rubber powder and waste nylon fiber. In step (2), the amount of epoxidized soybean oil added is 7.8-18.5% of the total amount of waste tire rubber powder and waste nylon fiber added; the amount of hydrogen peroxide added is 2.6-9.3% of the total amount of waste tire rubber powder and waste nylon fiber added. In step (3), the amount of the second mixture added is 120-205 parts by mass; the amount of the hyperbranched polyester added is 5-10% of the amount of the second mixture added; the amount of the plasticizer added is 3-6% of the amount of the second mixture added; the amount of the esterification catalyst added is 0.14-2.31% of the amount of the second mixture added; and the amount of the composite filler added is 2-5% of the amount of the second mixture added.
6. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recyclable materials according to claim 1, characterized in that: The composite filler in step (3) includes the following raw material components in parts by mass: 200-300 parts of fumed silica nanocomposite material, 90-110 parts of sodium montmorillonite, 0.5-1.5 parts of hexadecyltrimethylammonium bromide (first part), 15-25 parts of silane coupling agent (first part), 180-220 parts of ethanol, 100-200 parts of sodium silicate (first part), 60-80 parts of hydrochloric acid, 2-5 parts of hexadecyltrimethylammonium bromide (second part), 10-30 parts of carbon black, 8-10 parts of sodium hydroxide, 80-120 parts of lignocellulose, 350-450 parts of montmorillonite, and 10-15 parts of silane coupling agent (second part).
7. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recycled materials according to claim 6, characterized in that: The silica nanocomposite material comprises the following raw material components in parts by weight: 300-400 parts sodium disilicate, 10-20 parts sodium sulfate, 5-10 parts polyethylene glycol, 100-150 parts n-heptane, 20-40 parts sulfuric acid, 50-100 parts 11-aminoundecanoic acid, and 0.5-1 parts antioxidant 1010.
8. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recycled materials according to claim 7, characterized in that: The preparation method of the precipitated silica nanocomposite material includes the following steps: Sodium disilicate and sodium sulfate are mixed, polyethylene glycol and n-heptane are added and mixed, and then sulfuric acid is added and mixed to obtain a mixed solution; After mixing 11-aminoundecanoic acid, antioxidant 1010, and the mixed solution, the mixture was dried to obtain a mixed powder. The mixed powders were polymerized under vacuum to obtain a silica nanocomposite material.
9. The preparation method of an environmentally friendly direct-injection modified regeneration agent suitable for asphalt pavement recycled materials according to claim 6, characterized in that: The preparation method of the composite filler is as follows: Sodium montmorillonite and a first portion of hexadecyltrimethylammonium bromide are mixed, and a first silane coupling agent and ethanol are added and mixed to obtain mixture 1; Sodium silicate and hydrochloric acid were mixed, and then hexadecyltrimethylammonium bromide and carbon black were added and mixed to obtain mixture 2. Sodium hydroxide and lignocellulose were mixed, and then montmorillonite was added and mixed to obtain mixture 3; Mixture 1, mixture 2, and mixture 3 are mixed together, and then a second silane coupling agent and a silica nanocomposite material are added and mixed to obtain a composite filler.
10. An environmentally friendly direct-injection modified recycler suitable for asphalt pavement recycled materials, characterized in that: It is prepared by the method described in any one of claims 1-9.